DESIGN, SYNTHESIS, AND DOCKING OF SULFADIAZINE SCHIFF BASE SCAFFOLD FOR THEIR POTENTIAL CLAIM AS INHA ENOYL-(ACYL-CARRIER-PROTEIN) REDUCTASE INHIBITORS - Thangavelu, Prabha; Thangavel, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: An effort was made to design and synthesize the series of sulfadiazine building blocks as a targeted candidate for antimycobacterial activity. Method: The synthesized compounds were subjected to preliminary in silico screening study for testing their antimycobacterial action by doing their molecular docking study on bioinformatics software, molecular operating environment 2009.10. Result: The results obtained from this tool showed that there is a best docking affinity score of these target compounds against the enzyme InhA Enoyl-(acyl-carrier-protein) reductase from Mycobacterium tuberculosis (MTB) pathogen, which is one of the key enzymes involved in the type II fatty acid biosynthesis pathway of MTB. Conclusion: Thus, the synthesized sulfadiazine Schiff base derivatives might serve as the best drug candidate for the existence of menacing pathogen MTB. Â